Biostratigraphical controls on timing and rate of thrusting in the external zones of the Betic Cordillera, southern Spain - Woodward, Jason Mark (UCL (University College London), 2003)
The External Zones of the Betic Cordillera in Southern Spain comprise an obliquely convergent thin-skinned fold and thrust belt, active through much of the Miocene. During thrusting, a number of small inter-connected sedimentary basins formed on the upper surface of the thrust wedge, and were involved to varying degrees in the deformation. These basins provide an opportunity to date the inception and termination of both thrusting and strike-slip faulting at several locations across the belt, and hence of determining the rates of deformation and the rate of advance of the thrust front. Work concentrated on a series of basins in the eastern Subbetic and Prebetic belts on a transect from Lorca to Villacarillos, where good exposure, stratigraphic control, and the existence of seismic lines have allowed the construction of balanced sections across the thrust belt, so that the amount of shortening is known. Micropalaeontological biostratigraphy (based on planktonic foraminifera and calcareous nannofossils) provides refined controls for stratigraphic correlation and timing of tectonic events. The thrust front advanced rapidly, covering the distance to the Prebetic front within 14 Ma, and possibly in as little as 10 Ma. This timing is discussed in light of estimates for shortening along the same transect. The rapid rate of advance of the thrust front was accompanied by intervening periods of shortening and out-of-sequence thrusting within the thrust wedge. The Subbetic Frontal Thrust was active after the thrust front had progressed into the Internal Prebetic. The degree of partitioning of the strike-parallel component of motion also varied during evolution of the wedge. Biostratigraphy and field mapping have allowed timing of motion on the Socovos Fault to be re-evaluated, and episodes of deformation on the Crevillente Fault to be identified. The results are discussed in terms of mechanical models describing the partitioning of deformation in oblique convergence.